PERBANDINGAN KEKUATAN OTOT DAN MASSA OTOT ANTARA WANITA LANSIA AKTIF DAN TIDAK AKTIF BEROLAHRAGA - Della Hestia Suyanto; Cindra Paskaria; Decky Gunawan (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2021)
is a process of slowly losing the tissue's ability to maintain normal function and causing changes in muscle structure and function. A decrease in strength and muscle mass is a problem that often found in the elderly. Exercise is one of the factors that affect strength and muscle mass. The objective of the research is to compare the strength and muscle mass in elderly women who act and not actively exercise. This study is an observational analytic study with a cross-sectional design analyzed by an independent T-test. The research subjects were taken by purposive sampling, 20 elderly women aged over 60 years who met the inclusion and exclusion criteria were assessed for sports activity, muscle strength, and muscle mass so that it is obtained a sample of 13 elderly who are actively exercising and 7 elderly who are not actively exercising. Handheld muscle strength research data was measured using a handgrip dynamometer, muscle mass was measured using the Bioimpedance Analysis (BIA) method, and exercise habits were taken from the modification of the Baecke Physical Activity questionnaire. The results show that the elderly who were active in exercising with a mean score of muscle strength (10.59 ± 3.62) and muscle mass (34.22 ± 4.62) were higher than those who did not exercise (6.51 ± 3.42) and (29.81 ± 3.39) with p-values of 0.020 and 0.0125. There is a difference between strength and muscle mass in elderly women who are active and not actively exercising.